Functional outcomes of all-inside arthroscopic anterior talofibular ligament repair with loop suture versus free-edge suture - Shi-Ming Feng; Chang-Qing Shao; Qing-Qing Sun; Francesco Oliva; Nicola Maffulli (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Anatomic repair of anterior talofibular ligament (ATFL) is used to manage chronic lateral ankle instability (CLAI). However, the optimal suture configuration used to repair the ATFL is not yet determined. It remains unclear whether suture configuration affects clinical outcomes in such patients. Purpose To compare the functional outcomes of all-inside arthroscopic ATFL repair using either a loop suture and or a free-edge suture configuration in CLAI patients. Study Design Cohort study; Level of evidence, 3. Methods This retrospective cohort study included 71 patients with CLAI who had undergone an all-inside arthroscopic ATFL repair procedure with either loop suture (n = 36) or free-edge suture (n = 35) from February 2016 to July 2018. Comparable pre-operatively, the Visual analogy score (VAS), American Orthopedic Foot and Ankle Society scoring system (AOFAS), Karlsson Ankle Functional Score (KAFS) scoring system, Anterior Talar Translation (ATT) and Active Joint Position Sense (AJPS) were used to evaluate postoperative ankle function. Results There were no postoperative wound complications, implant reactions, or neurological or vascular injuries. Postoperative hospitalization, VAS, AOFAS, KAFS, AJPS and the time of return to sport were similar between the loop suture group and free-edge suture group. Requiring a longer procedure time, patients with loop suture configuration achieved better ATT. Conclusion All-inside arthroscopic ATFL repair procedure for CLAI treatment provides better ATT and comparable functional outcomes when a loop suture configuration is used instead of a free-edge suture configuration. A statistical difference in ATT was observed. Given the relatively short follow-up, it is questionable whether this will have any clinical relevance.